On the attractivity of an integrodifferential system with state-dependent delay - Bete, Kora Hafiz; Ogouyandjou, Carlos; Diop, Amadou; Diop, Mamadou Abdoul (My University, 2019)
This work is focused on the existence and attractivity of mild solutions for an integrodifferential system with state dependent delay. The results presented here were established by means of a fixed point theorem due to [T. A. Burton, C. Kirk, Math. Nachr., 189 (1998), 23–31]. At the end, the obtained results are illustrated by an example.
Journal of Nonlinear Sciences and Applications
Many phenomena in real life as thermodynamics, electrokinetics, biology, and chemistry can not be described by the classical differential equations. For these phenomena, the integrodifferential equations are more appropriate.
Keywords: Neutral functional integrodifferential equations; resolvent operator; mild solution; local attractivity; fixed point theory; infinite delay